Preserved or enhanced OATP1B3 expression in hepatocellular adenoma subtypes with nuclear accumulation of β‐catenin. Issue 10 (24th December 2014) - Fukusato, Toshio; Soejima, Yurie; Kondo, Fukuo; Inoue, Masafumi; Watanabe, Masato; Takahashi, Yoshihisa; Aso, Tatsuya; Uozaki, Hiroshi; Sano, Keiji; Sanada, Yukihiro; Niki, Toshiro
Abstract : Aim: Recent studies have indicated that hepatocellular adenoma (HCA) is a heterogenous group of benign tumors with various genetic and clinicopathological characteristics. We delineated the clinicopathological characteristics of HCA subtypes and evaluated the expression of transporter protein OATP1B3 in HCA. Methods: HCA in 34 Japanese patients were investigated immunohistochemically and classified into four subtypes (HNF1α‐inactivated type, H‐HCA; β‐catenin‐activated type, b‐HCA; inflammatory type, I‐HCA; unclassified type, u‐HCA). Immunostaining of OATP1B3 protein in HCA tissue sections was performed to determine the association between OATP1B3 expression and HCA subtypes. Results: HCA was categorized into the following four subtypes and two combined subtypes: 10 H‐HCA (29%), 10 I‐HCA (29%), seven b‐HCA (21%), two b‐HCA/H‐HCA (6%), two b‐HCA/I‐HCA (6%) and three u‐HCA (9%). The male‐to‐female ratio was 18:16. Oral contraceptive use was rare but seven HCA were found in patients with glycogen storage disease, congenital absence of the portal vein and idiopathic portal hypertension. OATP1B3 expression was decreased in 24 HCA but was preserved or increased in 10 HCA. All nine HCA with nuclear staining for β‐catenin showed preserved or enhanced OATP1B3 expression, indicating a significant association between nuclear β‐catenin accumulation and OATP1B3 expression in HCA. Conclusion: HCA subtype classification was validated in 91% of our Japanese subjects although their clinical backgrounds including rare contraceptive use were different from European subjects. A close association between preserved or enhanced OATP1B3 expression and b‐HCA subtype indicated important modalities for clinical decisions in the treatment and follow up of patients with HCA.